2020
DOI: 10.1590/1984-3143-ar2020-0526
|View full text |Cite
|
Sign up to set email alerts
|

Low invasive estrous synchronization protocol for wild animals: an example with melengestrol acetate in brown brocket deer (Mazama gouazoubira)

Abstract: Deer are sensitive to stressful stimuli by handling and their reproductive physiology could be altered by these procedures, making it necessary to develop less invasive protocols for ART. Melengestrol acetate (MGA), a synthetic progestin administered orally, appears as an alternative for estrous synchronization protocols (ESP), such as reported in cattle. Firstly, we compared two MGA doses (0.5 and 1.0 mg/day/animal), which would have suppression effect in estrous behavior (EB). Eight females were randomly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
2
6
0
Order By: Relevance
“…In the present study, 100% of females showed behavioral estrus approximately 44 hours after the end of the protocol. Similar success (100%) was previously reported for S. gouazoubira using the same oral progesterone 30 . Thus, the MGA-based estrus synchronization protocol is indicated for its high e ciency and for improving the welfare of the managed females, reducing stress sources, and offering more excellent safety to animals and technicians.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the present study, 100% of females showed behavioral estrus approximately 44 hours after the end of the protocol. Similar success (100%) was previously reported for S. gouazoubira using the same oral progesterone 30 . Thus, the MGA-based estrus synchronization protocol is indicated for its high e ciency and for improving the welfare of the managed females, reducing stress sources, and offering more excellent safety to animals and technicians.…”
Section: Discussionsupporting
confidence: 87%
“…Due to a high-stress stimulus when handling the animal 7,38,42 , which may alter their physiological reproductive parameters 43 . With this regard, oral synthetic progestagens, such as melengestrol acetate (MGA), are an e cient option for estrus synchronization in deer species 30,44 and domestic ruminants [45][46][47][48] . In the present study, 100% of females showed behavioral estrus approximately 44 hours after the end of the protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melengestrol acetate (MGA) can be administered to individuals with food at a dose of 1.0 mg/animal/day and is recommended to be divided into two periods of the day (morning and afternoon). The MGA-based protocol was applied in M. americana, M. nana, and M. nemorivaga, being used in a reproductive management routine for natural mating or artificial insemination procedures [94,95].…”
Section: Control Of the Estrous Cycle And Artificial Inseminationmentioning
confidence: 99%
“…Using 250 IU of FSH dissolved in polyvinylpyrrolidone, less than one CL per animal was observed (0.80 ± 0.49) [102]. Another protocol tested a 700 IU of eCG and obtained 6.0 ± 1.7 CLs, while the application of 130 mg of FSH divided into eight equal doses resulted in 2.0 ± 0.3 CLs [94]. Despite obtaining better SOV responses in treatments where higher doses of eCG were used, this hormone caused a premature regression of the CL, indicating possible poor follicle quality [103].…”
Section: Multiple Ovulation and Embryo Transfermentioning
confidence: 99%